PELATIHAN IMPLEMENTASI STRATEGI PEMBELAJARAN NUMERASI DI SDN 14 CAKRANEGARA - Hidayati, Vivi Rachmatul; Amrullah; Jufri, A. Wahab; Sukardi (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
Numeracy is one of the basic skills that students must have, especially students in elementary schools. Meanwhile, SDN 14 Cakranegara is one of the school partners that has implemented the Kurikulum Merdeka. Thus, reforms are needed in the implementation of learning, especially numeracy. Teachers at SDN 14 Cakranegara need refreshment regarding implementing numeracy learning that is fun and meaningful for students. Therefore, the service team intends to carry out training on the implementation of numeracy learning for elementary school teachers. This service goes through a process of preparation, implementation and evaluation (reporting). The training method is carried out by presenting material and implementing numeracy learning practices. The training was held on November 25 2023 with participants being teachers at SDN 14 Cakranegara. The training includes presentation of material, numeracy learning practice, and discussion. After that, an evaluation was carried out and the participants' responses to the activities were explored. A total of 9-11 participants stated that they understood numeracy and were able to explain numeracy across the curriculum in school learning